Autism theory - Chown, Nick (Henry Stewart Talks, 2019)
Why is autism theory important?, Theory and practice developed by autistic scholars, Evaluating theory, “Mainstream” autism theory, Monotropism, Criteriological understanding of the mind, Various other theories of autism, Double empathy, A synthesis of autism theory, Theory in practice, with a focus on monotropism